Improving Route Discovery for AODV to Prevent Blackhole and Grayhole Attacks in MANETs - Jhaveri, Rutvij H.; Patel, Sankita J.; Jinwala, Devesh C. (INFOCOMP Journal of Computer Science, 2012)
Design of basic routing protocols along with inherent characteristics of Mobile Ad-hoc Networks(MANETs)makes them vulnerable to various types of Do Sattack sat the network layer. Forsecure data transmission in wireless shared medium, communication route must be kept free from adversaries. In this paper, we provide a secure route discovery mechanism for MANETs using Ad-hoc On-demand Distance Vector (AODV) routing protocol against two of the most common Denial-of-Service (DoS) attacks, Blackhole attack and Grayhole attack that disrupt route discovery process by sending forged routing information. In our solution, a node detects unusual routing information when it receives route reply from misbehaving neighbor node launching attack and alerts other nodes about the adversary without using additional control packets; routing packets are used not only to pass routing information, but also to propagate information about malicious nodes. The solution isolates multiple malicious nodes during route discovery process and assures selection of short and secure route to destination. Simulation results in ns-2 prove the reliability and efficiency of our protocol.